The Rights of the Stillborn Child in Poland – Status de lege lata and Postulates de lege ferenda - Sobczyk, Paweł (Children's Rights in the Sustainable and Digital Environments: Exploring Opportunities and Challenges, 2025)
The legal status of stillborn children is a subject of interest for lawyers specializing in various branches of law. Therefore, the studies organized by the Institute of Justice in Warsaw (Poland) involved experts in civil law, family law, criminal law, law on civil status records, and medical law. The research confirmed the dispersion of regulations concerning the legal protection of stillborn children and the necessity of respecting the inherent dignity of human beings. According to the Constitutional Tribunal's judgment of May 28, 1997 (K 26/96), „Human life at every stage of its development constitutes a constitutional value subject to protection. However, this does not mean that the intensity of this protection at every stage of life and under all circumstances must be the same. The intensity and type of legal protection are not a straightforward consequence of the value of the protected good”.